Strategy to increase the fresh durability of water spinach (Ipomea aquatica) at a room temperature of 10⁰ C using packaging technology - Alif Maulana Alhafizh; Efrida Lubis; Wan Mohd Reza Ikwan bin Wan Hussin (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Water spinach (Ipomoea aquatica) is a leafy vegetable widely consumed in Southeast Asia; however, it rapidly deteriorates after harvest. This study evaluated the effect of passive modified atmosphere packaging (MAP) using low-density polyethylene (LDPE) films—both unperforated and perforated with 1% holes—on the postharvest quality of water spinach during cold storage at 10 ± 1 °C. The experiment was arranged in a completely randomized design with two packaging treatments and three sampling intervals (0, 5, and 10 days). The LDPE film without holes (T₁) created a passive modified atmosphere characterized by a gradual decrease in O₂ levels (to approximately 8%) and a concomitant increase in CO₂ levels (to approximately 3%), whereas the LDPE film with holes (T₂) maintained gas levels close to ambient. A significant interaction between treatment and time (p < 0.001) was observed for chlorophyll content, gas composition, and storage losses. Water spinach in T₁ exhibited lower cumulative storage losses and better chlorophyll retention compared to T₂, indicating a slower physiological decline under reduced O₂ and elevated CO₂ conditions. Overall, passive modified atmosphere packaging (MAP) using non-perforated LDPE film effectively maintained visual freshness and minimized water spinach quality losses for up to 10 days. Based on the comparison of T₁ and T₂ treatments, T₁ was superior, as observations up to the tenth day showed only a slight percentage loss in T₁ relative to T₂, likely due to the completely sealed packaging used in T₁.